The Position of the Witness and Victim Protection Agency (LPSK) in the Indonesian Criminal Justice System - Herlyanty Yuliana Angraeny Bawole; Grace Y. Bawole (Faculty of Law, Universitas Pekalongan, 2024)
The objective of this research is to understand the position of the Witness and Victim Protection Agency (LPSK) in the Indonesian Criminal Justice System. The research uses the library research method, which involves studying books, legislation, and other written materials related to the subject matter used by the author for this paper. The purpose of the Witness and Victim Protection Agency is to protect and provide a sense of security from any form of threat or intimidation from perpetrators of criminal acts that may influence the truth in the enforcement of criminal law. The position of LPSK in the criminal justice system plays an important role in establishing comprehensive protection for witnesses and victims.Keywords : Witness and Victim Protection Agency, Criminal Justice System